Tortoise Beetle, Chelymorpha cribraria (Fabricius) (Insecta: Coleoptera: Chrysomelidae) - Michael C. Thomas (EDIS)
This document is EENY-089 (originally published as DPI Entomology Circular No. 363), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.